An Analytical Study on Household Income and Consumption Patterns in District Bagh, Azad Jammu & Kashmir (Al-Qamar, 2024)
The research is an experimental exploration of the domestic income and expenditure in district Bagh AJ&K (Pakistan). The study utilized primary data of March 2020 gathered through a well-developed cum comprehensive questionnaire. It comprised a sample of 400 households selected through random sampling technique. The outcome was analyzed by applying “ordinary least square” (OLS) “regression model” and ANOVA test. Results of the study showed that relationship between income of household and domestic consumption is positive and significant. It means that the increase in the domestic income also increases their consumption. This result also contented the Keynesian theory on consumption. There is no significant impact occurred to take the gender of household and consumption. So, this study omits this variable from the model. There was a positive and substantial relationship existed between household age and domestic consumption. Households’ education and domestic consumption also had a constructive and meaningful relation. It means that educated people spend more as compare to less educated. There was a negative and noteworthy relationship existed between family structure and household consumption. Family size and household consumption had been also completely correlated. Nonetheless, the research determined that both economic factors and demographic features affect household consumption pattern in district Bahg AJ&K. Policy makers should formulate policies designed to increase the income level of employees for enhancing their buying power, decreasing their deficit and to increase their saving which would definitely ensure a sophisticated living standard of the study area.
Keywords: Household; Income; Consumption; Saving; Deficit